Comparative Assessment of the Influence of the IOL Position on the Aberrometry Parameters after Suture Fixation of the IOL-Capsule Bag Complex to the Iris - V. N. Nikitin; D. I. Ivanov (Oftalʹmologiâ)
Relevance. Suture fixation of dislocated IOL capsule-sac complexes to the iris is widely used at present. Violation of the correct position of the IOL affects the decrease in contrast sensitivity, the appearance of dysphotopsias and aberrations. Determining the dependence of the parameters of the IOL position on the quantitative characteristics of wave front aberrations in the delayed period will allow us to consider the applied methods of surgical treatment from the position of influencing the quality of vision.Purpose: to conduct a comparative assessment of the effect of IOL tilt and decentration on aberrometry indicators in the delayed postoperative period in patients with suture fixation of the IOL capsular-bag complex to the iris.Patients and methods. The main group consisted of 46 eyes operated on in 2014–2016 for the dislocation of capsule-bag complex by suture fixation to the iris for 2 arches. Comparison group — 30 eyes with articulation without suture fixation, having high uncorrected visual acuity (0.8–1.0). According to the study design, the indicators of both groups were determined at least 5 years after the operation. All patients had spherical IOLs. The determination of the IOL position (tilt and decentration) was carried out on RTVue OCT (Optovue, USA). Aberrometry was carried out on the OPD-Scan III, a comparative assessment of the wavefront indicators was performed: the mean square error of the total wavefront (Total RMS), general internal aberrations, tilt aberrations — “tilt”, total high-order aberrations “high”, oblique ray aberrations “Coma”.Results. Indicators of the IOL position. The main group. The average value of the angle of inclination in the horizontal meridian of the IOL was 3.07 ± 0.35°, in the vertical meridian 2.35 ± 0.25°. The decentration relative to the center of the pupil was 387.0 ± 3.4 mkm in the horizontal meridian, 443.0 ± 4.3 mkm in the vertical meridian. The comparison group. The average value of the angle of inclination in the horizontal meridian of the IOL was 3.04 ± 0.35°, in the vertical meridian 1.43 ± 0.13°. The decentration relative to the center of the pupil was 190.0 ± 2.8 mkm in the horizontal meridian, 259.0 ± 3.4 mkm in the vertical meridian. Aberrometry indicators. The main group: total RMS 0.52 ± 0.04, total internal aberrations 0.96 ± 0.04, tilt aberrations — “tilt” 0.31 ± 0.02, total high-order aberrations “high” 0.29 ± 0.01, oblique ray aberrations “Coma” 0.201 ± 0.010. The comparison group: total RMS 0.29 ± 0.03, total internal aberrations 0.66 ± 0.08, tilt aberrations — ““tilt” 0.202 ± 0.02, total high-order aberrations “high” 0.19 ± 0.07, oblique ray aberrations “Coma” 0.088 ± 0.010.The differences in the compared groups were significant (p < 0.05).The calculation of the correlation coefficient, when comparing the parameters of IOL decentration and the quantitative characteristics of aberrations, revealed a weak positive dependence, which indicates a slight influence of the obtained IOL decentration parameters on both internal aberrations and the RMS integral indicator.Conclusion. Thus, a comparative assessment of the indicators of the IOL position (tilt / decentration) and the number of wave front aberrations did not reveal a significant correlation. The correct central position of the IOL reduces wavefront aberrations and ensures high quality of vision. The method of suture fixation of the capsule-bag complexes to the iris provides a high functional and qualitative result in a delayed period.